From applied ethics to innovation practice: an ethics-by-design approach for constructive consideration of ELSI in technological design decisions - Jan Mehlich; Christiane Woopen (Journal of Responsible Innovation)
The manifold ethical, legal, and societal implications (ELSI) of new and emerging technologies are often elicited and dealt with too late in the innovation process which creates severe challenges and risks for regulators, appliers, and users as well as society as a whole. We conceptualised an ethics-by-design approach that allows innovators to incorporate normative reflections into their designs, translate ethical commitments into plausible design choices, and operate in interdisciplinary discourse settings competently. This article demonstrates the practical applicability of the concept by the example of the ELSI-SAT Health & Care online tool that is designed to aid researchers, developers and designers of medical and care technologies in integrating ethical, legal and societal considerations into their innovation work. It is shown that it has the power to elicit, analyse, understand, and control the ethical implications of design choices at an early stage of the technology development process, and to facilitate decision-making in line with ethical values.